Preventing Health Problems Impact toward Pesticide Exposure among Rice Farming Group in Mayang Village, Mayang District, Jember Regency: Upaya Pencegahan Masalah Kesehatan Dampak Pajanan Pestisida Pada Kelompok Petani Padi Di Desa Mayang Kecamatan Mayang Kabupaten Jember - Kholid Rosyidi Muhammad Nur; Dodi Wijaya; Nurfika Asmaningrum (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2023)
Indonesia is an agrarian society where most of the population work as farmers. Technological advances in this century have penetrated not only the field of telecommunications but also agriculture. This progress has made agricultural production increase but has also been accompanied by an increase in the use of pesticides. The problems caused by pesticide exposure include skin diseases and respiratory and digestive tract diseases. This community service aims to prevent health problems, especially the impact of pesticide exposure on the Ambarukmo rice farmer group in Mayang Village, Jember Regency. The service activity was carried out on May 22, 2022, and was attended by 26 farmers who are members of the Ambarukmo Farmer Group in Mayang Village. Activities include outreach, counseling, and handing over personal protective equipment to farmers. The counseling material includes an understanding of pesticides, the impact of pesticides on health, and efforts to prevent diseases caused by pesticides. Efforts to prevent health problems related to the impact of pesticide exposure on farmer groups to improve the health status of farmers so that they can remain productive and prosperous.